Sửa x(x - y) = 3/10
Ta có: \(\frac{x\left(x-y\right)}{y\left(x-y\right)}=\frac{\frac{3}{10}}{\frac{-3}{50}}\)\(\Rightarrow\frac{x}{y}=\frac{3}{10}.\frac{50}{-3}=-5\)\(\Rightarrow x=-5y\)
Lại có: \(x\left(x-y\right)=\frac{3}{10}\)\(\Rightarrow\left(-5y\right)\left(-5y-y\right)=\frac{3}{10}\)\(\Rightarrow\left(-5y\right)\left(-6y\right)=\frac{3}{10}\)\(\Rightarrow30y^2=\frac{3}{10}\)\(\Rightarrow y^2=\frac{3}{10}\div30=\frac{1}{100}\)\(\Rightarrow\orbr{\begin{cases}y=\frac{1}{10}\\y=\frac{-1}{10}\end{cases}}\)\(\Rightarrow\orbr{\begin{cases}x=-5.\frac{1}{10}=-\frac{1}{2}\\x=-5.\left(\frac{-1}{10}\right)=\frac{1}{2}\end{cases}}\)
Vậy....